# Deriving Fields of Moving Point Charge From Jemenko's equations

Seng Chien Yeah March 26, 2010

The Jemenko's equations are given by:
⃗ r E(⃗, t) ⃗ r B(⃗, t) = = ˆ ˙ ⃗r 1 ρ(⃗′ , tr ) r ρ(⃗′ , tr ) ˙ r J(⃗′ , tr ) ′ [ η+ η− ]dτ 4πϵ0 η2 cη c2 η ˆ ⃗ ′ ˙ ⃗r µ0 J(⃗ , tr ) J(⃗′ , tr ) r [ + ] × ηdτ ′ 4π η2 cη

Where ⃗ ≡ ⃗ − ⃗′ , η = |⃗ − ⃗′ | and tr ≡ t − η . A moving point charge has its η r r r r c charge and current density as the following:
ρ(⃗′ , tr ) = qδ 3 (⃗′ − w(tr )) r r ⃗ ′ 3 ′ ⃗r J(⃗ , tr ) = q⃗ (tr )δ (⃗ − w(tr )) v r ⃗

What we need to do now is to plug the charge and current density into the Jemenko's equations, and then evaluate the integral. But before this let's do some preparation work. We dene: ⃗′′ ≡ ⃗′ − w(tr ), because later we'll r r ⃗ do a change of integration varibale from ⃗′ to ⃗′′ . Also, we need to know the r r ∂x′ i general expression of ∂x′′ . It is evaluated as the following (notice that Einstein's j summation is assummed throughout the whole working):
⃗′ r ∂x′ ⇒ ∂x′′ ∂y ′ ∂x′′ ∂z ′ ∂x′′ ≡ ⃗′′ + w(tr ) r ⃗ 1 ∂x′ ∂y ′ ∂z ′ = 1 + vx (tr ){ηx ′′ + ηy ′′ + ηz ′′ } cη ∂x ∂x ∂x ′ ′ ′ ∂x ∂y ∂z 1 = vy (tr ){ηx ′′ + ηy ′′ + ηz ′′ } cη ∂x ∂x ∂x 1 ∂x′ ∂y ′ ∂z ′ = vz (tr ){ηx ′′ + ηy ′′ + ηz ′′ } cη ∂x ∂x ∂x

Solving these three linear equations, we obtain:
∂x′ ∂x′′ = 1+ 1 1−
⃗ ·η v c

1 vx ηx cη

1

∂y ′ ∂x′′ ∂z ∂x′′ ′ = = 1 1− 1 1− ⃗ ·η v c ⃗ ·η v c 1 vy ηx cη 1 vz ηx cη To be parallel with Griths. tr ) = = ∂tr qδ 3 (⃗′ − w(tr )) r ⃗ ′′ ∂⃗ r q · ∇′′ δ 3 (⃗′′ ) r ∂tr −q⃗ (tr ) · ∇′′ δ 3 (⃗′′ ) v r ∂tr {q⃗ (tr )δ 3 (⃗′ − w(tr ))} v r ⃗ 3 ′′ q⃗ (tr )δ (⃗ ) − q⃗ (tr ){⃗ (tr ) · ∇′′ δ 3 (⃗′′ )} a r v v r Finally we recall that when we change the integration variable from ⃗′ to ⃗′′ . tr ) = ˙ r = = ˙ ′ ⃗r J(⃗ . so the previous result can u v be written in the following general form: ∂x′ 1 i ′′ = δij + ⃗ · ⃗ vi ηj ∂xj u η Next we need the expression of derivaties of certain functions with respect to ⃗′ (the reason will be clear later). 2 . so we just quote the results: ′ ∂k η ′ ∂k (η)i ′ ∂k vi ′ ∂k ui c 1 (η)i (η)k − ai (η)k η c 1 ′ a η ∂k (⃗ · ⃗ ) = −c(η)k − (⃗ · ⃗ )(η)k + vk u η c = −(η)k 1 = − δik + η 1 = ai (η)k c c = − δik + η 1 (η)i (η)k η The third thing to know is how to take time derivative on the charge and current density. r r the integration measure also suers a change: dτ ′ = 1 1− ⃗ ·η v c dτ ′′ = cη dτ ′′ ⃗ ·⃗ u η This feature was discussed in the class when we learned the Lienard-Wiechert potential. There's no diculty at all in the derivation r (the only point to remember is that all functions with time-dependence are evaluated at the retarded time). we dene ⃗ = cη − ⃗ . It can be easily done using chain rule: ρ(⃗′ .

tr ) ˙ r ηdτ ′ 4πϵ0 cη ˆ q 1 = − η{⃗ (tr ) · ∇′′ δ 3 (⃗′′ )}dτ ′′ v r 4πϵ0 ⃗ ·⃗ u η ˆ q ⃗η v = [∇′′ · { }]δ 3 (⃗′′ )dτ ′′ r 4πϵ0 ⃗ ·⃗ u η We have performed an integration by part to obtain the last line. t) are independent variables.Now we have everything prepared so we can start our job. tr ) ′ r dτ 4πϵ0 c2 η ˆ 1 q⃗ (tr )δ 3 (⃗′′ ) − q⃗ (tr ){⃗ (tr ) · ∇′′ δ 3 (⃗′′ )} ′′ a r v v r − dτ 4πϵ0 c⃗ · ⃗ u η ˆ q⃗ a q ⃗ (tr ){⃗ (tr ) · ∇′′ δ 3 (⃗′′ )} ′′ v v r − + dτ 4πϵ0 c(⃗ · ⃗ ) 4πϵ0 c u η ⃗ ·⃗ u η ˆ q⃗ a q ⃗⃗ vv − − [∇′′ · { }]δ 3 (⃗′′ )dτ ′′ r 4πϵ0 c(⃗ · ⃗ ) 4πϵ0 c u η ⃗ ·⃗ u η − ˆ = = = Now we can add all three terms together. The nal expression is a vector. One point here to be emphasized: before doing the integration. ⃗′ and (⃗. r r however after carrying out the integration. There are three ⃗ terms in the E -formula. It goes as: ˆ 1 ρ(⃗′ . and the rst term reads: ˆ 3 ′′ q δ (⃗ ) r ηdτ ′ 4πϵ0 η2 ˆ 3 ′′ qc δ (⃗ ) 1 r η dτ ′′ 4πϵ0 η ⃗ ·⃗ u η qc η 4πϵ0 η(⃗ · ⃗ ) u η = = The integration is done using the delta-function. and proceed to the third term. ⃗′ becomes a function of (⃗. with its ith component given by: q 4πϵ0 ˆ ′′ [∂j { vj (η)i 3 ′′ }]δ (⃗ )dτ ′′ r ⃗ ·⃗ u η Before carrying out the actual integration. let's just leave it there. t) given r r implicitly by: ⃗′ = w(t − r ⃗ |⃗ − ⃗′ | r r ) c We then evaluate the second term. and otain: ⃗ E= qc q⃗ a q η− + 4πϵ0 η(⃗ · ⃗ ) u η 4πϵ0 c(⃗ · ⃗ ) 4πϵ0 c u η [∇′′ · { ⃗⃗ vu }]δ 3 (⃗′′ )dτ ′′ r ⃗ ·⃗ u η 3 . which reads: ˆ ⃗ ′ ˙ 1 J(⃗ .

This is probably the most dicult part. as described previously.⃗⃗ vu We have to evaluate ∇′′ · { ⃗ ·⃗ } before carrying out the integration using deltauη function. so we just stop at this point. say ith component. and 2nd line to 4th line. It goes as: = = = = = = ⃗⃗ vu })i ⃗ ·⃗ u η ′′ vj ui ∂j { } ⃗ ·⃗ u η ∂x′ ′ vj ui k ∂ { } ∂x′′ k ⃗ · ⃗ u η j 1 ′ vj ui {δjk + vk ηj }∂k { } ⃗ ·⃗ u η ⃗ ·⃗ u η 1 1 ′ ′ ′ {δjk + vk ηj } {(⃗ · ⃗ )(vj ∂k ui + ui ∂k vj ) − vj ui ∂k (⃗ · ⃗ )} u η u η ⃗ ·⃗ u η (⃗ · ⃗ )2 u η 1 ′ ′ ′ [(⃗ · ⃗ ){vk ∂k ui + ui ∂k vk } − vk ui ∂k (⃗ · ⃗ ) u η u η (⃗ · ⃗ )2 u η 1 ′ ′ ′ u η v η {(⃗ · ⃗ )[(⃗ · ⃗ )vk ∂k ui + ui ηj vk ∂k vj ] − (⃗ · ⃗ )ui vk ∂k (⃗ · ⃗ )}] u η v η + ⃗ ·⃗ u η 1 c c 1 1 {vk [− δik + (η)i (η)k − ai (η)k ] + ui ⃗ · η} a ⃗ ·⃗ u η η η c c 1 1 − v u {−c(η)k − (⃗ · ⃗ )(η)k + vk } a η 2 k i (⃗ · ⃗ ) u η c c c 1 1 ⃗ ·⃗ v η {vk [− δik + (η)i (η)k − ai (η)k ] + ui ⃗ · η} a + 2 (⃗ · ⃗ ) u η η η c c ⃗ ·⃗ v η 1 − vk ui {−c(η)k − (⃗ · ⃗ )(η)k + vk } a η (⃗ · ⃗ )3 u η c (∇′′ · { Adding 1st line to 3rd line. so I'll present the calculation as clear as possible. After this. we evaluate the integral using delta-function δ 3 (⃗′′ ). which results in all ⃗′ taking r r denite value. we get: c c 1 1 cη {vk [− δik + (η)i (η)k − ai (η)k ] + ui ⃗ · η} a 2 (⃗ · ⃗ ) u η η η c c cη 1 − vk ui {−uk − (⃗ · ⃗ )(η)k } a η (⃗ · ⃗ )3 u η c 1 1 c {cui − c(⃗ · η)(η)i − (⃗ · ⃗ )ai + (⃗ · ⃗ )ui } u v η a η = 2 (⃗ · ⃗ ) u η c c c 1 − {−η(⃗ · ⃗ )ui − (⃗ · ⃗ )(⃗ · ⃗ )ui } v u a η v η (⃗ · ⃗ )3 u η c c2 ui c2 (η)i (⃗ · ⃗ )ai v η cη(⃗ · ⃗ )ui v u cη(⃗ · ⃗ )ui a η = − − + + (⃗ · ⃗ )2 u η η(⃗ · ⃗ ) u η (⃗ · ⃗ )2 u η (⃗ · ⃗ )3 u η (⃗ · ⃗ )3 u η The last line is simple enough. 4 . Let's evaluate one component of it.

The magnetic eld can be worked out accordingly.In the last step we put all the pieces together. hence we've successfully derived the electric eld produced by a single moving point charge. producing: ⃗ E = qcη q⃗ a q c2 ⃗ u c2 η (⃗ · ⃗ )⃗ v η a − + { − − 2 4πϵ0 η(⃗ · ⃗ ) 4πϵ0 c(⃗ · ⃗ ) 4πϵ0 c (⃗ · ⃗ ) u η u η u η η(⃗ · ⃗ ) (⃗ · ⃗ )2 u η u η cη(⃗ · ⃗ )⃗ v u u cη(⃗ · ⃗ )⃗ a η u + + } (⃗ · ⃗ )3 u η (⃗ · ⃗ )3 u η qc⃗ u qη⃗ a qη(⃗ · ⃗ )⃗ v uu qη(⃗ · ⃗ )⃗ a η u + − + + 2 3 ⃗ · ⃗ )2 4πϵ0 (⃗ · ⃗ ) u η 4πϵ0 (⃗ · ⃗ ) u η 4πϵ0 (⃗ · ⃗ )3 u η 4πϵ0 (u η c qη [−(⃗ · ⃗ )⃗ + (⃗ · ⃗ )⃗ + (⃗ · ⃗ )⃗ + (⃗ · ⃗ )⃗ ] u η a u η u v uu a η u 4πϵ0 (⃗ · ⃗ )3 u η η qη c [−(⃗ · ⃗ )⃗ + (⃗ · ⃗ )⃗ + (⃗ · ⃗ )⃗ + (cη · ⃗ − v 2 )⃗ ] u η a a η u u η u v u 4πϵ0 (⃗ · ⃗ )3 u η η qη [⃗ × (⃗ × ⃗ ) + (c2 − v 2 )⃗ ] η u a u 4πϵ0 (⃗ · ⃗ )3 u η = = = = This is exactly (10.65) of Griths' textbook. so we will not write it down here. 5 .